(untitled) (KSV Journal of Pharmacy and Health Sciences, 2024)
Herbs have been used in both the olden days and the modern time because they contained natural ingredients and had minor side effects. Antioxidant drugs or additives are so multivalent in health benefits. In normal metabolism, there occurs oxidation leading to release of free radicals causing cell damage. The cell damage can lead to the higher diseases like diabetes, cancer, and obesity. Intake of antioxidants can help in preventing these diseases through relieving oxidative stress and minimizing the damage caused to cells by free radicals, which lead to better health and well-being.We selected four plants for the present study: Brassica nigra(seeds), Mentha piperita(fresh leaves), Glycyrrhiza glabra (stem), and Cyperus rotundus(rhizome). Four independent assays were done to evaluate antioxidant activity, which consisted of two scavenging assays and two chemical assays. Ascorbic acid was the standard. Results obtained showed that Brassica nigra and Cyperus rotundus have higher antioxidant activities than the other two plants.